[PP.19.09] APELIN AND VISFATIN PLASMA LEVELS IN HEALTHY INDIVIDUALS WITH HIGH NORMAL BLOOD PRESSURE. (September 2016) - Papadopoulos, D.; Sanidas, E.; Perrea, D.; Grassos, H.; Liakos, C.; Barbetseas, J.; Makris, T.
Abstract : Objective: High normal blood pressure (BP)(130–139/85–89 mmHg) seems to be related with increased cardiovascular risk compared to normal BP (120–129/80–84 mmHg) or/and optimal BP (<120/80 mmHg). Low apelin plasma levels have been associated with arterial hypertension and atherosclerosis while high visfatin plasma levels may promote vascular inflammation and atherosclerotic plaque destabilization and have been evaluated as a marker for identifying stages of essential hypertension. We sought to compare the apelin and visfatin plasma levels between subjects with high normal BP and subjects with normal or optimal BP matched for age, gender, smoking, and body mass index (BMI). Design and method: Twenty-five subjects with high normal BP (office BP 136 ± 3/88 ± 2 mmHg, age 57 ± 4 years, 76% males, 32% smokers, BMI 24.0 ± 1.7 kg/m2) and 35 subjects with normal or optimal BP (office BP 118 ± 2/78 ± 2 mmHg, age 55 ± 7 years, 63% males, 29% smokers, BMI 23.2 ± 1.4 kg/m2) were studied. The apelin and visfatin plasma levels were determined with the enzyme-linked immunosorbent assay. Results: Compared to normal or optimal BP subjects, apelin levels were significantly lower (205 ± 108 vs. 325 ± 152 pg/ml, p < 0.001) and visfatin levels significantly higher (11.0 ± 2.0 vs. 7.2 ± 0.9 ng/ml, p = 0.002) in high normal BP subjects. No significant differences were found between the 2 groups (p = NS) regarding the basic clinical characteristics, the glycemic/lipid profile and the renal function parameters. Conclusions: The emerging, from the present study, lower apelin and higher visfatin plasma levels in high normal BP subjects compared to normal or optimal BP individuals may partially explain the higher cardiovascular risk of the high normal BP group.